Innovative Synthesis of PANI/Cu2O Nanocomposite and Its Antibacterial Properties. Issue 47 (16th December 2021) - Zhang, Mengmeng; Han, Sha; Niu, Xiaohui; Li, Hongxia; Zhang, Deyi; Fan, Haiyan; Wang, Kunjie
Abstract: To fight various bacteria‐caused inflammations and overcome drug resistance, the present work develops a simple in‐situ growth method to synthesize Cu2 O nanoparticles involved nanocomposite using polyaniline (PANI) matrix. The morphology of the as prepared composite was characterized by Scanning Electron Microscope (SEM) and X‐ray Diffraction Spectroscopy (XRD), and the molecular structure was identified using Fourier‐Transforms Infrared FT‐IR, X‐ray Photoelectron Spectroscopy (XPS), and UV‐Visible Spectroscopy (UV‐Vis). The antibacterial properties of PANI/Cu2 O nanocomposite were tested against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), and Methicillin‐resistant Staphylococcus aureus (MRSA) . The combination of PANI and Cu2 O indicated a synergistic antibacterial effect. The analysis of the antimicrobial mechanism revealed that the positive charge released from the nanocomposite takes the main responsibility. This work provides new ideas for the design of metal oxide and polymer nanocomposites and the development of antibiotics. Abstract : This paper uses the properties of polyaniline to disperse cuprous oxide in the matrix, which is not easy to oxidize in the air, effectively avoids the accumulation of Cu2 O itself, and uniformly releases Cu + to have a certain destructive effect on the peptidoglycan located in the cell wall. Active oxygen can cause DNA decomposition, and the electrostatic adsorption effect of polyaniline and the release effect of Cu + from Cu2 O perform synergistic antibacterial action, effectively inhibiting the growth of bacteria.